The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jid.2017.07.846
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Overexpression of Xenobiotic Receptor PXR Impairs the Epidermal Barrier and Triggers Th2 Immune Response

Abstract: The skin is in daily contact with environmental pollutants, but the long-term effects of such exposure remain underinvestigated. Many of these toxins bind and activate the pregnane X receptor (PXR), a ligand-activated transcription factor that regulates genes central to xenobiotic metabolism. The objective of this work was to investigate the effect of constitutive activation of PXR in the basal layer of the skin to mimic repeated skin exposure to noxious molecules. We designed a transgenic mouse model that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Tregs exposed to phenanthrene show decreased TGF‐β and IL‐10 and increased IL‐4, IL‐13, (p)STAT6 and GATA‐3 . It has recently been shown that repeated exposure to air pollution and to noxious molecules may promote AD . Thus, pollutants may contribute to AD also via their ability to affect Treg populations, especially by impeding their immunosuppressive capacity by causing them to redifferentiate into Th‐like cells that produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tregs exposed to phenanthrene show decreased TGF‐β and IL‐10 and increased IL‐4, IL‐13, (p)STAT6 and GATA‐3 . It has recently been shown that repeated exposure to air pollution and to noxious molecules may promote AD . Thus, pollutants may contribute to AD also via their ability to affect Treg populations, especially by impeding their immunosuppressive capacity by causing them to redifferentiate into Th‐like cells that produce proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, AD prevalence is relatively high, affecting 15%‐30% of children and 2%‐10% of adults. Notably, AD prevalence has markedly increased during the past 40 years, potentially because of a higher pollution burden …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major advance came with the genetic demonstration that significant numbers of AD patients had FLG deficiency that compromises the epidermal barrier, allowing penetration of bacteria, allergens, and environmental chemicals and pollutants. Increases of these xenobiotics in urban regions combined with barrier access has been shown to act on keratinocytes to trigger the transcription factor PXR (Elentner et al, 2018) and the aryl hydrocarbon receptor, both of which can work to cause AD worsening and even downstream release of TSLP and activation of the T helper (Th) type 2 pathway (Hidaka et al, 2017).…”
Section: Epidermal Barriermentioning
confidence: 99%